Expenditure and Displacement effects of Students in the Periphery: Impact on the Scottish Highlands and Islands - Kristinn Hermannsson (European Regional Science Association (ERSA), 2015)
A ubiquitous feature of life in peripheral communities is that school leavers have to move away to attend further and higher education. From the point of view of an individual student and his family significant amounts have to be spent to pay for term time costs. These are at least partially funded through saving incomes earned locally. These term time expenditures are then spent at the place of study, typically a central city. This gives rise to a spatial demand-shift effect, where students increase consumption where they study and reduce consumption where they are from. Because of this, the location of HEIs can have an important impact not only upon their host economies but also on the localities where students originate from. This paper analysis the flow of students within Scotland and the resulting spatial shift of consumption expenditures. The focus is on the peripheral region of the Highlands and Islands (HI) and its interaction with the Rest of Scotland (ROS). Student records data are used to determine the origin and destination of HE students in Scotland. This reveals a significant net-outflow of students from the HI to the ROS. Using survey-based expenditure profiles and a custom built 2-region Input-Output table the economic impact of these student flows are estimated for both sending and receiving regions.
Keywords: I23; I25; R12; R15; 330; Input-Output; Impact; Higher Education; Students; Expenditures; Displacement